Childhood cultures in transformation : 30 years of the UN convention of the rights on the child in action towards sustainability - Ødegaard, Elin Eriksen; Borgen, Jorunn Spord (Brill | Sense, 2021)
"This book investigates and uncover paradoxes and ambivalences that are actualised when seeking to make the right choices in the best interests of the child. The 1989 United Nations Convention on the Rights of the Child established a milestone for the 20th century. Many of these ideas still stand, but time calls for new reflections, empirical descriptions and knowledge as provided in this book. Special attention is directed to the conceptualisation of children and childhood cultures, the missing voices of infants and fragile children, as well as transformations during times of globalisation and change. All chapters contribute to understand and discuss aspects of societal demands and cultural conditions for modern-day children age 0-18, accompanied by pointers to their future. Contributors are: Eli Kristin Aadland, Wenche Bjorbækmo, Elin Eriksen Ødegaard, Eldbjørg Fossgard, Ida Marie Lyså Hege Wergedahl, Susanne Højlund Petersen, Asle Holthe, Liisa Karlsson, Karen Klitgaard Povlsen, Jonatan Leer, Czarecah Oropilla, Anja Maria Pesch, Gro Rugseth, Jorunn Spord Borgen, Stinne Gunder Strøm Krogager, Liv Torunn Grindheim, Kristin Vindhol Evensen, Pauline von Bonsdorff and Susanne C. Ylönen"--